New horizons in understanding oral health and swallowing function within the context of frailty. (2nd February 2023) - Robison, Raele; (Focht) Garand, Kendrea L; Affoo, Rebecca; Yeh, Chih-Ko; Chin, Nathaniel; McArthur, Caitlin; Pulia, Michael; Rogus-Pulia, Nicole
Abstract: Frailty is a complex and multidimensional condition wherein declines in physiologic reserve and function place individuals in a state of heightened vulnerability and decreased resiliency. There has been growing interest in both research and clinical settings to understand how to best define, assess and characterise frailty in older adults. To this end, various models and clinical assessment tools have been used to define and measure frailty. While differences exist among these models and tools, a common unifying theme is a focus on physical function and activity. Notably absent across many available conceptual models and clinical tools are items directly related to oral and swallowing function. This is an important oversight as widespread changes to both oral and swallowing function are evident in older adults. Indeed, emerging evidence suggests many of the functional domains affected in frail older adults, such as nutrition and sarcopenia, have cyclical relationships with impairments in oral (oral hypofunction) and swallowing function (dysphagia) as well. The increasing appreciation for the interrelationships among oral hypofunction, dysphagia and frailty provides an opportunity for refinement of frailty assessment and characterisation in older adults to incorporate metrics specific to oral and swallowing function.